Egested Feces Revealed Massive Protein Loss in 99mTc-HSA-D Scintigraphy. (July 2020) - Matsusaka, Yohji; Nakahara, Tadaki; Iwabuchi, Yu; Owaki, Yoshiki; Narimatsu, Hidetoshi; Jinzaki, Masahiro
Abstract : Abstract: A 66-year-old man with severe diarrhea and severe hypoproteinemia was referred for 99m Tc-DTPA-human serum albumin (HSA-D) scintigraphy. The scintigraphy at 24 hours postinjection showed strong accumulation of 99m Tc-HSA-D in not only the colon but also all his diapers containing his egested feces. The ratio of the diapers counts to the total counts was 17.0%, and a considerable amount of protein loss was confirmed. 99m Tc-HSA-D scintigraphy has an important role in diagnosing protein-losing enteropathy, but the abdomen is the only routinely scanned area. Additional scanning of egested radiotracer and the whole body can be useful for evaluating the disease severity.